Die Abenteuer von Huck Finn - Twain, Mark 1835-1910; Twain, Mark 1835-1910 (Buena Vista Home Entertainment, 2002)
Huck Finn, a 19th-century boy floating down the Mississippi River on a raft with Jim, a runaway slave, becomes involved with a feuding family, two scoundrels pretending to be royalty, and Tom Sawyer's aunt, who mistakes him for Tom.
Orig.: USA 1993
Keywords: Twain, Mark -- 1835-1910 -- The adventures of Huckleberry Finn; Boys -- Drama; Finn, Huckleberry (Fictitious character) -- Drama; Fugitive slaves -- Drama; Runaway children -- Drama; Literatur; Junge; Flucht; Abenteuerfilm; Ausreißer; Verfilmung; Sklave; Mississippi River -- Drama; Mississippi-Gebiet; DVD-Video; Adventure films; Children's films; Feature films; Film adaptations; Video recordings for the hearing impaired